1992
DOI: 10.1002/jmv.1890380313
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors inducing the persistence of high‐risk genital papillomaviruses in the normal cervix

Abstract: To evaluate the risk factors associated with persistence of human papillomaviruses (HPV) types 16, 18, and 33 in the normal cervix, a prospective study was carried out in Belgium of 323 women without cytological evidence of cervical intraepithelial neoplasia. Demographic and clinical data were obtained by interview, and HPV DNA was assayed in cervical-swab specimens using the Fast Multiplex Polymerase Chain Reaction-based screening and confirmatory tests. A multivariable linear regression model was constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…It will also identify situations where the frequency of HPV infection is so high relative to the frequency of neoplasias as to make HPV testing irrelevant. However, it has been shown that not all the HPV infections progress to oral cancer and that some of the precancerous lesions regress spontaneously (5). Therefore, some additional factors, environmental or endogenous, must modulate the evolution of HPV in the oral tissue.…”
mentioning
confidence: 99%
“…It will also identify situations where the frequency of HPV infection is so high relative to the frequency of neoplasias as to make HPV testing irrelevant. However, it has been shown that not all the HPV infections progress to oral cancer and that some of the precancerous lesions regress spontaneously (5). Therefore, some additional factors, environmental or endogenous, must modulate the evolution of HPV in the oral tissue.…”
mentioning
confidence: 99%
“…Nine found no correlation between CHPI and OC use [4,7,[8][9][10][22][23][24][25], although the odds ratios were more than 1.0 in most studies. In five studies [5, [26][27][28][29], the OC use was significantly correlated with CHPI. One of these studies [5] adjusted for number of lifetime sexual partners but no other sexual risk behavior factors.…”
Section: Discussionmentioning
confidence: 96%
“…One of these studies [5] adjusted for number of lifetime sexual partners but no other sexual risk behavior factors. One study [27] addressed the problem of OC type between monophasic and triphasic OCs, but did not stratify into different potencies. Three previous studies [5,9,23] have included data on duration of OC use.…”
Section: Discussionmentioning
confidence: 99%
“…Although other cervical infections have been suggested as cofactors for activation of latent HPV in the cervix, 23 larger trials where multivariate analyses are possible would be needed to test for potential independent cofactors in HPV DNA expression.…”
Section: Hiv Hpv and Dysplasia Eckert Et Almentioning
confidence: 98%